Effect of hawthorn vinegar-based marinade on the quality parameters of beef tenderloins - Karatepe, Pinar; Akgol, Muzeyyen; Incili, Canan Akdeniz; Tekin, Ali; Incili, Goekhan Kuersad; Hayaloglu, Ali Adnan (Elsevier, 2023)
In the current study, it was hypothesized to evaluate the potential effects of hawthorn vinegar-based marinade at 3 different concentrations (25%, 50%, and 100%) and marination duration (2, 6, and 24 h) on the physico-chemical, microbiological, textural properties, microstructure, and sensory attributes of tenderloins. It was also aimed to identify and quantify the bioactive compounds present in the hawthorn vinegar that contribute to the aforementioned properties of tenderloins. The levels of organic acids, individual phenolic and flavonoid com-pounds, volatiles, in-vitro antioxidant capacity (DPPH, ABTS, and FRAP) of the hawthorn vinegar were analyzed. In addition, minimum inhibitory concentration (MIC), and inhibition zones were determined against Escherichia coli O157:H7, Salmonella Typhimurium, S. Enteritidis, and Listeria monocytogenes strains. A total of five organic acids, 21 phenolic and flavonoid compounds and 51 volatiles were determined in the hawthorn vinegar, and displayed strong antioxidant capacity determined by DPPH (470.93 +/- 28.55 mg TEAC/L), ABTS (706.03 +/- 4.88 mg TEAC/L) and FRAP (59.15 +/- 0.50 mM FE/L) tests. The MIC and inhibition zones of the hawthorn vinegar ranged between 5.21 and 6.25%, and 9.41-11.43 mm against tested pathogens, respectively. In the tenderloin experiment, all marination treatments significantly changed the physicochemical and textural properties, microbiological status, and microstructure of the tenderloins (P < 0.05). Among them, the most effective treatment was the marination with 100% hawthorn vinegar for 24 h. In this treatment, the hardness, chewiness, springiness, and gummines values of the tenderloins were found lower than untreated tenderloins (P < 0.05). Furthermore, this treatment provided a high reduction in the number of pathogens ranging between 3.08 and 3.82 log(10) CFU/g (P < 0.05) compared to the control. Although no differences were found among the groups (P > 0.05), flavor, odor, appearance, texture, and color scores of the tenderloins marinated with 100% hawthorn vinegar for 24 h were found higher than the non-marinated samples. The results of this study revealed that hawthorn vinegar contains certain levels of bioactive compounds which can help to improve the microbiological quality and textural properties of the meat parts.
Keywords: Marination; Hawthorne vinegar; Tenderloin; Microbial inhibition; Quality parameters